Toxicity study of lead naphthenate. Issue 3 (July 1974) - Peteghem, Th. Van; Devos, H.
Abstract : van Peteghem, Th., and de Vos, H. (1974). British Journal of Industrial Medicine, 31, 233-238. Toxicity study of lead naphthenate. Lead naphthenate is added to oils and greases in order to increase their resistance to high pressures. Experiments on animals and humans showed the possibility of a small amount of percutaneous absorption. An investigation was performed on technicians regularly dealing with these lubricants in order to explore to what extent they had absorbed the lead naphthenate. The degree of absorption was evaluated by measuring the lead content of the blood and the δ-aminolevulinic acid concentration in the urine. Individual results did not permit clearcut conclusions whether an increase in lead absorption had occured or not. Therefore the group of technicians was compared with a group without any occupational contact with lead-containing lubricants but otherwise comparable in occupational and general exposure to lead. To test the significance of the difference between the means of the samples a one-sided t test not assuming equal standard deviations for both populations was used. For any of two compared populations the t test was repeated after rejection of the larger values which were 2·5 standard deviations from the mean value in the exposed population. It appeared that the lead concentration in the blood and the δ-aminolevulinic acid concentration in the urine of people exposed to lead naphthenate-containing lubricants were significantly higher than those concentrations observed in non-exposed persons.